The Effect of 8 Weeks of Corrective Exercises Using the NASM Approach on Movement Disorders, Lumbar Lordosis, and Genu Valgum in Girls Aged 12-15 - Arefeh Samadi; Behrouz Hajilou (Islamic Azad University, Hamedan Branch, 2024)
Objective The purpose of this study was to determine the effect of 8 weeks of corrective exercises with the NASM approach on movement disorders, lumbar lordosis, and genu valgum in 12-15-year-old girls. Methods Forty-five teenage girls were divided into three groups, including a movement disorder group (N=15), a lumbar lordosis group (N=15), and a genu valgum group (N=15). The corrective exercises program with the NASM approach included 24 sessions over 8 weeks with a frequency of 3 sessions per week. A flexible ruler, caliper, goniometer, and the scoring form of the NASM approach were used to measure variables. Dependent t-tests and Mann-Whitney U tests were used to analyze the data at a significance level of p<0.05. Results The results showed that performing 8 weeks of corrective exercises with the NASM approach reduced movement disorders from the anterior view, including flattening of the right foot (p = 0.02), inward movement of the right (p = 0.01) and left (p = 0.03) knees, and from the lateral view, it included low back arches (p = 0.01). Additionally, from the posterior view, flattening of the feet (p = 0.01) and asymmetrical weight shifting to the right (p = 0.01) and left (p = 0.02) showed significant improvement. Furthermore, these exercises had a significant effect on the lumbar lordosis angle (p = 0.011) and Q angle (p = 0.032), but did not produce a substantial effect on the medial malleolus distance (p = 0.086). Conclusion According to the results of the present research, it is suggested to use a corrective exercise program with the NASM approach to prevent and reduce movement disorders, and correct genu valgum and lumbar lordosis.